Origin and geodynamic environments of the metamorphic sole rocks from the İzmir–Ankara–Erzincan suture zone (Tokat, northern Turkey). Issue 15 (17th November 2016) - Çörtük, Rahmi Melih; Çelik, Ömer Faruk; Özkan, Mutlu; Sherlock, Sarah C.; Marzoli, Andrea; Altıntaş, İsmail Emir; Topuz, Gültekin
ABSTRACT: The Late Cretaceous accretionary complex of the İzmir–Ankara–Erzincan suture zone, near Artova, is composed mainly of peridotites (variably serpentinized), amphibolite, garnet-micaschist, calc-schist, marble, basalt, sandstones, neritic limestones. The metamorphic rocks were interpreted as the metamorphic sole rocks occurring at the base of mantle tectonites, because: (i) amphibolites were observed together with the serpentinized peridotites suggesting their occurrences in the oceanic environment; (ii) foliation in amphibolites and serpentinized peridotites run subparallel to each other; (iii) all these metamorphic rocks and serpentinized peridotites are cross-cut by the unmetamorphosed dolerite dikes with island arc tholeiite-like chemistry. Geochemical characteristics of the amphibolites display enriched mid-ocean ridge basalt (E-MORB)- and ocean island basalt (OIB)-like signatures. The dolerite dikes, on the other hand, yield an island arc tholeiite-like composition. Geothermobarometric investigations of the metamorphic sole rocks suggest that the metamorphic temperature was ~650 ± 30°C and the pressure condition was less than 0.5 GPa. Dating of hornblende grains from amphibolite yielded age values ranging from 139 ± 11 to 157 ± 3.6 Ma (2 σ ). The oldest weighted average age value is regarded as approximating the timing of the intra-oceanic subduction. These cooling ages were interpreted to be the intra-oceanic subduction/thrusting time of the İzmir–Ankara–Erzincan oceanic domain.